Association of prenatal folate status with early childhood wheeze and atopic dermatitis - Roy, Aditi (Pediatr Allergy Immunol, 2017)
BACKGROUND: Prenatal folic acid supplementation is recommended to prevent birth defects. Some foods are fortified in the U.S. to ensure sufficient intake among reproductive-aged women. However, high prenatal folate exposure may be a risk factor for childhood atopic diseases. We investigated associations between prenatal folate and early childhood wheeze and atopic dermatitis in a U.S. cohort. METHODS: We studied 858 mother-child dyads, enrolled prenatally. Folate was measured in 2(nd) and 3(rd) trimester maternal plasma. Parents reported current wheeze (previous 12 months) and healthcare provider diagnosis of atopic dermatitis at 3 years. We examined associations using logistic regression, modeling folate continuously and dichotomously (< or ≥20 ng/ml), a level often considered supraphysiologic. RESULTS: Over half of women were African-American and on Medicaid. Median (interquartile range) folate levels were 22.6 (15.9–30.0) and 23.1 (16.1–30.0) ng/mL for 2(nd) and 3(rd) trimesters, respectively. Current wheeze and atopic dermatitis were reported for 20.4% and 26.8% of children, respectively. Second trimester folate as a continuous exposure was not significantly associated with outcomes. Decreased odds of current wheeze was observed in children born to mothers who had 2(nd) trimester folate ≥ 20 ng/mL (adjusted odds ratios = 0.67, 95% confidence interval = 0.46, 0.97) compared to children with maternal levels < 20 ng/mL. Third trimester folate was not associated with outcomes. CONCLUSIONS: High plasma folate in mid-pregnancy was associated with decreased odds of current wheeze at age 3. Our findings do not support harmful effects of high prenatal folate levels on childhood atopic diseases in this setting.